RISET PEMETAAN SISTEM INFORMASI MANAJEMEN PADA KEDAI KOPI DI INDONESIA - Kurniawanto, Hadi; Hanafiah, Hafidz (LPPM Universitas Bina Bangsa, 2024)
Management information system (SIM) is management that uses an information system basis in running a system. This SIM is widely used in various sectors with the aim of making it easier for an organization to be effective and efficient. The aim of this research is to determine the mapping of Management Information Systems in coffee shops in Indonesia from various published journals. The method of this research is a literature study from journals related to coffee shop Management Information Systems. The results of this qualitative research show that Management Information Systems in coffee shops are still dominated by website-based systems, the rest are Android-based with various methods, one of which is the waterfall method. Use of this Management Information System for sales, management and ordering